DIAPASON ON MILITARY POWER IN TERM OF CONTEMPORARY GLOBALIZATION (Annual of the Faculty of Philosophy in Skopje, 2009)
Processes of globalization get primarity on regulations of the worldsaffaires. Controversies and revivals from the periods of Cold war. remainsbehind antagonisms who led toward series of wars and conflicts through theworld. Periods fulfillments of oscillations with peace and war, pointed at thatglobalization process and war how sociable phenomenon are not seen lakeseparated issues. The world composed of countries „classified“ how countriesfrom First. Second or Third world is difficult to find common peaceful solution.„Double standards“ promoted by globalization always remains possibility ofne w co 11 i s i on between, ,po wer ,,lights“ and,, interests ‘ ‘ on states and internationalorganizations.